IKLIM ORGANISASI DAN KUALITAS KEHIDUPAN KERJA KARYAWAN - Aryansah, Imam (Universitas Ahmad Dahlan, 2013)
AbstractThis study aims to test empirically the relationship betweenorganizational climate and the quality of work life of employees at PT AseliÂ Dagadu Djokdja. The sample is the whole employees of PT. Aseli DagaduÂ Djokdja. Data were collected through organization climate scale and qualityof work life scale. Product Moment Correlation was used as analysisÂ technique. Based on result of data analysis, there is positive correlationÂ between organizational climate and PT. Aseli Dagadu Djokdja employeeâsÂ quality of work life. The effective contribution of organization climate toÂ quality of work life was 48,4%.Keywords : organizational climate, quality of work life.